A preliminary experimental feasibility case study of energy upgrade of pellets of lignite and plastic waste mixtures. Issue 2 (26th January 2020) - Lasithiotakis, Michael; Zoumboulakis, Loukas; Soulis, Spyridon; Simitzis, Johannis
Abstract: The calorific value enhancement of lignite by briquetting with novolac resin and plastic wastes is discussed in this work. Mixtures of several types of lignite with novolac as binder, with or without polypropylene, were manufactured in the form of pellets by curing. Pellets were pyrolyzed at 300°C and 500°C, and weight losses were determined. Chemical transformations during curing were studied by Fourier‐transform infrared spectroscopy, and the corresponding changes in the microstructure of the pellets were investigated by optical microscopy. Specimens of cured pellets were tested for their impact resistance index (IRI) and water resistance index (WRI). The incorporation of polypropylene in the pellets leads to an increase of IRI and a decrease of WRI. The calorific value was measured for both cured and pyrolyzed pellets. All pellets exhibit increased lower calorific value compared with raw lignite, indicating an upgrade of their energy content.